Answer:
The difference can be expressed as
y=x³+120x²-4800x+64000
Or
y=(40-x)³
Explanation:
Step one
To solve the problem problem let us first initialize the number to be x
By breaking the statement into component parts and implementing
Step two
1. The difference between 40 and the number
=(40-x)
2. The cube of the difference
= (40-x)³
Let us equate the expression to y
y=(40-x)³
Step three
Expanding the expression we have
y= (40-x)(40-x)(40-x)
Opening bracket we have
y=(1600-40x-40x+x²)(40-x)
y=64000-1600x-
1600x+40x²-1600x+40x²+40x²-x³
y=x³+120x²-4800x+64000